The effect of a proposed training program using motor games, educational games, and (motor + educational) games on developing creative thinking in kindergarten children - Yaakoubi, fateh (sports creativity, 2025)
The aim of the research was to examine the effect of a program consisting of motor games, educational games, and (motor + educational) games on developing certain creative thinking abilities in kindergarten children aged 4-6 years, both in general and according to gender. The study included 60 students from the total population of 300, who were intentionally selected after the researcher excluded students who did not meet the study criteria. The students were divided into three equal groups in terms of boys and girls. The first group trained on the motor games program, the second group trained on the educational games, and the third group trained on the (motor + educational) games program. The educational program lasted for 8 weeks, with 40 games allocated to each program, distributed over 5 educational units per week. The researcher used the Torrance Tests of Creative Thinking and a questionnaire for kindergarten teachers designed by the researcher. The results of the study indicated that the programs used contributed to the development of certain creative thinking abilities in kindergarten children in general.